Changing Worship Practices in American Congregations - Roso, Joseph (Journal for the scientific study of religion, 2020)
Worship is the core activity of American congregations and the primary way people experience religion collectively in the United States. We use data from the National Congregations Study (NCS), notably including data from the fourth wave, collected in 2018-19, to examine two key trends in worship practices among American religious congregations. First, the trend toward more informal and enthusiastic worship identified in earlier NCS surveys continues into 2019. Showing no signs of having reached a plateau, a more informal worship style has increased in prevalence across every major American religious tradition. Second, recently developed communication technologies have permeated congregations’ worship services in ways that change the collective experience. Collected on the eve of the COVID-19 pandemic, NCS-IV data on worship and technology provide a baseline for future examinations of worship changes caused by the pandemic, and a window into congregations’ technological preparedness for a world in which it is not safe to gather.